Using musical pitch interval comparisons to assess cochlear implant frequency-to-place maps - Lewis, Rebecca M.; Gilbert, Melanie L.; Beim, Jordan A.; Oxenham, Andrew J.; Limb, Charles J. (Frontiers in Audiology and Otology, 2025)
IntroductionMusic perception remains challenging for many cochlear implant (CI) recipients, due perhaps in part to a frequency mismatch that can occur between the original tonotopic cochlear map and the allocation of frequencies along the electrode array that occurs during programming. Individual differences in ear anatomy, electrode array length, and surgical insertion can lead to great variability in the positions of electrodes within the cochlea, but these differences are not typically accounted for by current CI programming techniques.ObjectivesFlat panel computed tomography (FPCT) can be used to visualize the location of the electrodes and calculate the corresponding spiral ganglion characteristic frequencies. Such FPCT-based CI frequency mapping may improve pitch perception accuracy, and thus music appreciation, as well as speech perception. The present study seeks to develop a behavioral assessment metric for how well place-based pitch is represented across the frequency spectrum by evaluating the accuracy with which listeners perceive and compare pitch intervals across different frequency regions.MethodsThe study included two groups: normal-hearing (NH) listeners and CI recipients. Listeners were asked to match the pitch interval created by two tones, played sequentially, across different frequency ranges to estimate the extent to which pitch is evenly distributed across the CI array. This test was initially evaluated with pure tones in normal-hearing listeners, using both unprocessed and vocoder-processed sounds to simulate both matched and mismatched frequency-to-place maps. We hypothesized that the vocoded stimuli would be more difficult to match in terms of pitch intervals than unprocessed stimuli, and that a warped map (as may occur with current clinical maps) would produce poorer matches than a veridical and well-aligned map (as may be achieved using FPCT-based frequency allocation).ResultsPreliminary results suggest that the task can reveal differences between veridical and warped maps in normal-hearing listeners under vocoded conditions. A small cohort of CI recipients were tested with the same pure tone stimuli (without vocoding). Performance of the CI recipients was similar to that of normal-hearing listeners, and both groups showed less accurate interval matching compared to NH listeners.DiscussionThe results suggest promise for this method when comparing the perceptual effects on pitch interval perception of traditional clinical maps and FPCT-based frequency allocation.